Distribution of protein bodies and phytate-rich inclusions in grain tissues of low and high iron rice genotypes - C. Prom-u-thai (2018)
The present study aims to understand whether genotypic differences in grain iron (Fe) concentration in four rice genotypes are related to its association with protein bodies containing phytate-rich inclusions. Rice genotypes with high and low grain Fe concentrations in unpolished brown rice were grown in a greenhouse at Chiang Mai, Thailand, and grains were harvested at maturity. The presence of protein bodies and phytate-rich inclusions in rice grain tissues were examined by means of light and transmission electron microscopy (TEM). The composition of mineral elements in different grain tissues was examined using energy dispersive X-ray microanalysis (EDX) and chemical analysis. The relative distribution pattern of protein bodies in the tissues was similar among the four rice genotypes, which resembled the pattern of grain N concentrations in these tissues. The high grain Fe genotypes (based on brown rice Fe concentration) had more protein bodies containing phytate-rich inclusions in the embryo and aleurone layer tissues than the low Fe genotypes. Phytate-rich inclusions were not detected in the endosperm tissues in all genotypes. In conclusion, the presence of protein bodies with phytate-rich inclusions predominantly in the embryo and aleurone regions of the grain is an important parameter contributing to the variation in brown rice Fe concentration among the genotypes, but not in the white rice (the endosperm). Iron associated with the phytate-rich inclusions present in the embryo and aleurone layer tissues are largely lost during the polishing process to produce white rice. © 2008 AACC International, Inc.